Efficacy and safety of direct‐acting antiviral therapies and baseline predictors for treatment outcomes in hepatitis C patients: A multicenter, real‐world study in Guangdong, China. Issue 9 (31st May 2022) - Xie, Zhiwei; Deng, Kai; Xia, Yang; Zhang, Chunlan; Xu, Min; Li, Feng; Liu, Jinfeng; Zhou, Yuanping; Chen, Xiaoping; Chen, Xuefu; Yan, Qin; Huang, Jing; et al.
Abstract: The data on direct‐acting antivirals (DAAs) in chronic hepatitis C (CHC) patients in southern China with multiple genotypes circulating are limited. This study aims to evaluate the efficacy and safety of DAA regimens among CHC patients in Guangdong, China. A total of 220 patients receiving a variety of DAA were enrolled. The primary outcome was sustained virologic response (SVR) at 12 weeks. Resistance associated substitutions (RASs) were evaluated by deep sequencing. The overall SVR rate was 96.4%, and was 97.7% for genotype 1, 100% for genotype 2, 91.9% for genotype 3, 95.7% for genotype 6, and 100% for untyped. The overall incidence of adverse events (AEs) was 8.2% (18/220) and all the AEs were mild. Nonstructural proteins 5A RAS, 30K/31M, and Y93H were most prevalent at baseline and the end of treatment in non‐SVR patients, respectively. Logistics regression showed that elevated alanine aminotransferase (ALT) and aspartate aminotransferase (AST) at baseline were specifically associated with non‐SVR in patients with genotype 3 and 6 infections ( p  = 0.029 and p  = 0.017) but not genotype 1 infection ( p  = 0.746 and p  = 0.971), and baseline AST was the best predictor for SVR in genotypes 3 and 6 patients (area under curve = 0.890). Our studies demonstrated all DAA regimens achieved ideal SVR and were well tolerated. NS5A RAS were prevalent in non‐SVR patients. Elevated ALT and AST as baseline predictors for non‐SVR in genotypes 3 and 6 infections warrant further research in a larger cohort.